Cone ice crushing tests and simulations associated with various yield and fracture criteria. (13th March 2017) - Han, Donghwa; Lee, Heejeong; Choung, Joonmo; Kim, Hyunwook; Daley, Claude
ABSTRACT: To determine the most reliable numerical simulation parameters affecting the ice resistances, such as yield functions with relevant ice-breaking criteria, compressive volumetric hardening intensities and element sizes, numerical simulations for different parameters were compared with the crushing tests of cone-shaped ice specimens. The yield functions of crushable foam, Drucker–Prager and Mohr–Coulomb were taken into consideration with three different volumetric hardening intensities. The ice resistance variation was also studied for two finite element models with different element sizes. To realize ice breaking in numerical simulations, a damage variable was introduced to trigger fracture initiation and evolution. The nominal contact area-dependent energy per unit area as a damage to fracture was newly proposed from the test results composed of a crushing force versus indenter stroke. This new concept could be realized by applying the different nominal contact area-dependent fracture energies to finite elements along the vertical location.